Polymorphism and the analgesic activity of N-(3-pyridylmethyl)-4-hydroxy-2-oxo-1,2,5,6,7,8-hexahydroquinoline-3-carboxamide - Ukrainets, I. V.; Mospanova, O. V.; Bereznyakova, N. L.; Davydenko, O. O. (Journal of Organic and Pharmaceutical Chemistry, 2015)
The advanced study of the analgesic activity of N-(3-pyridylmethyl)-4-hydroxy-2-oxo-1,2,5,6,7,8-hexahydroquinoline-3-carboxamide selected by the results of the primary pharmacological screening as the leading structure has revealed a significant change in anesthetic properties in different samples of this compound. Since the substance under study was not soluble in water, and animals received it orally as a thin aqueous suspension, the most likely cause of the effect observed was thought to be the changes in the crystalline structure of N-(3-pyridylmethyl)-4-hydroxy-2-oxo-1,2,5,6,7,8-hexahydroquinoline-3-carboxamide occurring in it under the influence of external factors. This assumption has been fully confirmed by the thorough microscopic investigation of righ – and low-active samples, as well as more objective data, the methods of powder and single crystal X-ray diffraction analysis. Thus, in particular, it has been found that with all the variety of crystalline and amorphous forms included in the samples studied their qualitative composition appeared to be quite similar. At the same time the quantitative content of some of the phases varies greatly, and obviously, it was the factor determining the size of the analgesic effect.